Research and Design of Scalable Advanced Application Based on Dual-Core Smart Meter. Issue 1 (1st April 2022) - Guo, Xinglin; Zhang, Bensong; Fan, Xiaofei; Pan, Shenchen; Wu, Haowen
Abstract: The dual-core smart meter based on the embedded operating system adopts a new software and hardware architecture design, and is equipped with software and hardware resources suitable for scalable advanced applications, which can support application software to form a unified large-scale market. Based on the software and hardware platform of the dual-core smart meter, this paper designs and implements application management functions suitable for advanced applications, and the design realizes advanced functions such as load identification and contract power purchase. It verifies the powerful software and hardware platform expansion capabilities of the dual-core smart meter. It has laid a certain technical foundation for supporting the construction of next generation of smart meter application ecological market.